Sharia Ethics in Fintech Debt Collection: Evaluating SPinjam’s Compliance with Islamic Legal Principles - Husnul Khatimah; Abdul Gafar Saidi (Saqifah: Jurnal Hukum Ekonomi Syariah, 2025)
Sharia-based fintech lending has experienced rapid growth in Indonesia, including through the SPinjam feature that operates within the Shopee ecosystem. One of the most crucial aspects in ensuring the sharia compliance of these services is the mechanism for billing and imposing late fees, given the potential for elements of usury, gharar, and dzulm to arise if they are not applied in accordance with sharia provisions. Fatwa DSN-MUI No. 106/2016 emphasizes that penalties are only permitted as ta'zîr for debtors who can pay but deliberately delay payment, and that penalty funds must be channeled entirely to social activities and cannot be used for institutional profit. This study aims to analyze the suitability of the collection and penalty mechanisms for SPinjam in accordance with the fatwa's provisions. The research method used is a normative-empirical approach through regulatory studies, fatwa analysis, documentation of SPinjam's official policies, and observation of application features. The findings indicate inconsistencies, particularly regarding the lack of transparency in the allocation of penalty funds, the potential involvement of third parties in collection that may conflict with Sharia ethics, and the possibility of usury if penalties are categorized as income. In addition, no specific mechanism was identified to provide relief to debtors experiencing difficulties, thereby raising the possibility of injustice. This study recommends stricter Sharia audits, increased operational transparency, strengthening the role of the Sharia Supervisory Board (DPS), and harmonizing collection SOPs with the principles of justice, benefit, and legal certainty in Sharia.